The role of generative artificial intelligence in modern design: Theoretical considerations - Galkin, Dmitry V. (Вестник Томского государственного университета. Культурология и искусствоведение)
This paper explores the role of artificial intelligence (AI) in modern design, particularly focusing on the theoretical foundations of delegation of functional tasks. It begins by discussing the agency of things from an object-oriented approach and how it relates to AI. The concept of delegation is examined in detail, considering its meaning and implications for design. The capabilities of AI are analyzed, and different levels of AI development are presented. The paper then delves into the shift from humanism to nonhumanism in design, highlighting the changes brought about by generative AI, such as deep human-computer collaboration, data as a core resource, and systematic innovation. It also addresses issues like data quality, design originality, and the integration of AI in various design aspects. Additionally, it touches on AI governance and the influence of object-oriented ontology (OOO) on design thinking. Finally, it concludes that design should aim to maximize the quality of human-centered lives, while also acknowledging the growing importance of design synergy in complex cultures.